Wave diffraction and radiation by a fully-submerged body in front of a vertical wall by using an exact DtN artificial boundary condition. (June 2023) - Rim, Un-Ryong; Ri, Yong-Gwang; Do, Won-Chol; Dong, Pil-Sung; Kim, Chol-Won; Kim, Jin-Sim
Abstract: This paper is concerned with wave diffraction and radiation by an arbitrarily-shaped submerged body in front of a vertical wall. An artificial boundary is chosen as a virtual cylindrical surface so that it can enclose two bodies (one is the original body and another is its imaginary body by the method of mirror image), and the entire water domain is divided into an interior subdomain and an exterior one by the artificial boundary. An exact DtN artificial boundary condition on the artificial boundary is derived from an analytical solution in the exterior subdomain, and it is used as a boundary condition to solve hydrodynamic interaction of the bodies with the interior subdomain numerically using boundary integral equation. The present numerical model is validated by comparison with precedent analytical results in case of a submerged circular cylinder. The effects of heading angle, body submergence and distance from the wall on wave elevation and exciting forces are considered in case of a chamfer box or a capsule.